Churchill and the european tradition of liberty (Comillas Journal of International Relations, 2016)
Churchill believed in the existence of a specific political tradition of the English-speaking peoples. But he also clearly believed that tradition to be part of the European and Western tradition of liberty. This article tries to identify some of the crucial ingredients that Churchill attributed to the Anglo-American political culture and to its contribution to the broader European tradition. It also recalls Churchill’s political evolution – from the Conservatives to the Liberals in 1904 and back to the Conservatives twenty years later – trying to identify some of the main features of his political philosophy.
Keywords: Anglo-American and European political culture; Churchill’s political philosophy; enjoyment; free trade; limited government; revolution; reform.